WORKSHOP PEMBUATAN ONLINE ASSESSMENT UNTUK MENGHINDARKAN SISWA DARI PENYALAHGUNAAN CHATGPT BAGI GURU-GURU SEJARAH SMA/MA KOTA SOLOK - Syafril, Syafril; Rahmi, Ulfia; Ofianto, Ofianto; Azrul, Azrul (UNIVERSITAS PGRI MADIUN, 2024)
Abstract. Teachers' concerns about the development of AI, especially chatGPT, which provides opportunities for students to cheat, prompted the organization of an assessment workshop for teachers. Teachers' skills to design and conduct assessments of chatGPT abuse in history learning need to be improved. The goal is to prevent students from misusing chatGPT. The workshop training implementation activities were held in August 2023. The target audience in community service activities in the workshop for making online assessments are Solok city history teachers totaling 13 people. The problem found is that Solok City SMA/MA history teachers do not yet have the skills to design online assessments to avoid misuse of chatGPT by students. The problem was overcome by providing a workshop on making online assessments to prevent students from misusing chatGPT for teachers in the SMA/MA history MGMP of Solok City. The activity scenario consists of three steps. The first step is the introduction of AI technology in general. Second, the introduction of Chat GPT platform and technology and its function and online assessment application. The third step, designing an online assessment to minimize cheating with chatGPT. The success indicator of this workshop for MGMP history teachers is seen from the results of the pre and post-tests, as well as the results of the design of the online evaluation questions. Through this training, teachers have knowledge about AI and are able to design online assessments that minimize the misuse of chatGPT. Abstrak. Kekhawatiran guru-guru terhadap perkembangan AI terutama chatGPT yang memberikan peluang untuk siswa melakukan kecurangan mendorong untuk menyelenggarakan workshop pembuatan assessment bagi guru. Keterampilan guru untuk merancang dan melakukan penilaian terhadap penyalahgunaan chatGPT dalam pembelajaran sejarah perlu ditingkatkan. Tujuannya agar siswa terhidar dari penyalahgunaan chatGPT. Kegiatan pelaksanaan pelatihan workshop diselenggarakan pada bulan Agustus 2023. Khalayak sasaran dalam kegiatan pengabdian kepada masyarakat pada workshop pembuatan online assessment adalah Guru-guru sejarah kota solok yan berjumlah 13 orang. Permasalahan yang ditemukan bahwa guru-guru sejarah SMA/MA Kota Solok belum memiliki keterampilan untuk merancang online assessment untuk menghindarkan penyalahgunaan chatGPT oleh siswa. Permasalahan tersebut diatasi dengan memberikan workshop pembuatan online assessment untuk menghindarkan siswa dari penyalahgunaan chatGPT bagi guru-guru di mgmp sejarah SMA/MA Kota Solok. Skenario kegiatan terdiri dari tiga langkah. Langkah pertama adalah pengenalan teknologi AI secara umum. Kedua, pengenalan platform dan teknologi chatGPT dan fungsinya dan aplikasi online assessment. Langkah ketiga, merancang online assesmnet untuk meminimalisir kecurangan dengan chatGPT. Indikator keberhasilan workshop bagi guru MGMP sejarah ini dilihat dari hasil pre-test dan post-test, serta hasil rancangan soal evaluasi online yang dirancang. Melalui pelatihan ini, guru-guru mempunyai pengatahuan tentang AI dan mampu merancang online assessment yang memiminalisir penyalahgunaan chatGPT.